The Counselor’s Compass: Navigating Self-Growth Amidst Professional Challenges - Dewi Ilma Antawati; Bambang Raditya Purnomo (P3I UMSurabaya, 2024)
This study explores the challenges, skills, and self-development strategies counselors require counselors in various fields, including education, industry organization, and clinical. The approach used is qualitative research with a phenomenological design involving seven experienced counselors with at least three years of experience. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The study's results identified four main themes: problems often handled by counselors, counseling skills needed, factors causing burnout, and self-development activities. In education, the main challenges include student behavior problems and children with special needs. At the same time, in industry and organizations, counselors often deal with disciplinary problems and employee dissatisfaction. In the clinical field, counselors focus on cases of violence and legal assistance. The discussion shows that ongoing self-development and burnout mitigation strategies through time management and peer support are essential to improving the quality of counseling practice in all fields.